Controls of lithology and climate over chemical weathering trends: new insights from the precipitation-dominated Dokriani glacier, central Himalaya, India - Shipika Sundriyal; Tanuj Shukla; Shichang Kang; Yulan Zhang; Dwarika Prasad Dobhal; Rajesh Singh (Journal of Glaciology)
The chemical composition of meltwater-draining Himalayan glacierized basins reflects the dominance of carbonic acid in weathering of silicate and carbonate minerals, yet the role of sulfuric acid-mediated reactions in the mineral weathering and ionic release is still unclear. Here, we present a long-term study (1992–2018) of chemical weathering characteristics of a precipitation-dominated glacierized basin (Dokriani glacier) of central Himalaya. By using new and reprocessed datasets of major ions from the glacial/subglacial zones of the glacier, we suggest that two-thirds of the dissolved load of the meltwater derives from sulfuric acid-mediated weathering of minerals and rocks. We observed a clear control of carbonic acid-mediated reactions in the early ablation periods, while sulfuric acid-mediated reactions dominate in peak and late ablation periods. The slopes and intercepts in best-fit regressions of [*Ca2+ + *Mg2+ vs *SO42− and HCO3−] and [HCO3− vs *SO42−] in meltwater were following the stoichiometric parameters of sulfide oxidation coupled to carbonate dissolution reactions. The glaciers of the central and western Himalaya are in good agreement with the present estimates. We contend that the bedrock lithology has limited or second-order effects over the ionic release from Himalayan glaciers and surmise that these patterns are broadly applicable to the other orogenic systems of the world.